Growing pains with kratom: experiences discussed in subreddits contrast with satisfaction expressed in surveys - Rogers, Jeffrey M.; Colvin, Kayla; Epstein, David H.; Grundmann, Oliver; McCurdy, Christopher R.; Smith, Kirsten E. (Frontiers in Pharmacology, 2024)
Background: "Kratom" refers to an array of bioactive products derived from Mitragyna speciosa, a tree indigenous to Southeast Asia. Most kratom consumers report analgesic and stimulatory effects, and common reasons for use are to address mental and physical health needs, manage pain, and to reduce use of other substances. Natural-history studies and survey studies suggest that many kratom consumers perceive benefits from those uses, but such studies are unlikely to capture the full range of kratom-use experiences. Methods: We collected text data from Reddit posts from 2020-2022 to qualitatively examine conceptualizations, motivations, effects, and consequences associated with kratom use among people posting to social media. Reddit posts mentioning kratom were studied using template thematic analysis, which included collecting descriptions of kratom product types and use practices. Network analyses of coded themes was performed to examine independent relationships among themes, and between themes and product types. Results: Codes were applied to 329 of the 370 posts that comprised the final sample; 134 posts contained kratom product descriptions. As Reddit accounts were functionally anonymous, demographic estimates were untenable. Themes included kratom physical dependence (tolerance, withdrawal, or use to avoid withdrawal), perceived addiction (net detrimental effects on functioning), and quitting. Extract products were positively associated with reports of perceived addiction, dependence, and experiences of quitting kratom. Many used kratom for energy and self-treatment of pain, fatigue, and problems associated with opioid and alcohol; they perceived these uses as effective. Consumers expressed frustrations about product inconsistencies and lack of product information. Conclusions: As in previous studies, kratom was deemed helpful for some and a hindrance to others, but we also found evidence of notable negative experiences with kratom products that have not been well documented in surveys. Daily kratom use should be expected to produce mild-moderate physical dependence, with greater severity being more common with extracts, however there are currently no human laboratory studies on kratom extracts. Such studies, and detailed kratom product information, are needed to help inform consumer decision-making.